2010
DOI: 10.1142/s1793604710001354
|View full text |Cite
|
Sign up to set email alerts
|

MICROWAVE DIELECTRIC PROPERTIES AND RAMAN SPECTROSCOPY OF SCHEELITE SOLID SOLUTION [(Li0.5Bi0.5)1-xCax]MoO4 CERAMICS WITH ULTRA-LOW SINTERING TEMPERATURES

Abstract: A Scheelite solid solution was formed based on [( Li0.5Bi0.5 )1-x Ca x] MoO 4 ceramics and prepared via a solid state reaction method in the range 0.0 ≤ x ≤ 1.0. High performance microwave dielectric properties were obtained in the [(Li0.5Bi0.5)0.15Ca0.85]MoO4 ceramic sintered at 760°C with a relative permittivity of 14.1, a Qf value of 24,000 GHz (at 10.0 GHz), and a temperature coefficient value of +10.7 ppm/°C and the [(Li0.5Bi0.5)0.1Ca0.9]MoO4 ceramic sintered at 850°C with a relative permittivity of 12.7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…When these ions have the same coordination number, the ionic radius of Bi 3+ is larger than that of Sm 3+ , considering the ion of larger ionic radius replaces the small one, the volume of the unit cell may have a trend of expanding. It is observed that the intensity of (101) peak decreases with the increasing x value, this result is similar to the report about the scheelite materials doped bismuth compositions and the decreasing intensity of (101) peak may be associated with the disordering of the A‐site ion . The SEM micrograph of the [Ca 0.55 (Sm 0.05 Bi 0.95 ) 0.3 ]MoO 4 ceramic is observed from the inset of Figure and the surface microstructure shows uniformity and densification.…”
Section: Resultssupporting
confidence: 86%
“…When these ions have the same coordination number, the ionic radius of Bi 3+ is larger than that of Sm 3+ , considering the ion of larger ionic radius replaces the small one, the volume of the unit cell may have a trend of expanding. It is observed that the intensity of (101) peak decreases with the increasing x value, this result is similar to the report about the scheelite materials doped bismuth compositions and the decreasing intensity of (101) peak may be associated with the disordering of the A‐site ion . The SEM micrograph of the [Ca 0.55 (Sm 0.05 Bi 0.95 ) 0.3 ]MoO 4 ceramic is observed from the inset of Figure and the surface microstructure shows uniformity and densification.…”
Section: Resultssupporting
confidence: 86%
“…This relation has successfully explained the relationship between the Qf and the ε r of many scheelite solid solutions such as (Bi 1 − x Y x )VO 4 , [(Li 0.5 Bi 0.5 ) 1 − x Ca x ]MoO 4 and (Ca 1 − x Bi x )(Mo 1 − x V x )O 4 . Moreover, the facts show that the same qualitative relationship is also suitable for (Bi 1 − x Ce x )VO 4 (0 ≤ x ≤ 1) ceramics.…”
Section: Resultsmentioning
confidence: 63%
“…Therefore, the Qf value of (Bi 1 − x Ce x )VO 4 (0 ≤ x ≤ 1) ceramics shows an increasing trend. At microwave region, the Qf value has inverse relation to ε r Q×f)(ze2/mVε02πγ×εω-ε.…”
Section: Resultsmentioning
confidence: 99%
“…In Zhou's work [6], the [(Li 0.5 Bi 0.5 ) 0.1 Ca 0.9 ]MoO 4 ceramic sintered at 850 8C with a relative permittivity of 12.7, a Q Â f value of 41,300 GHz (at 10.3 GHz), but the expensive lithium oxide (Li 2 O) is a negative impact of cost-reducing. Many kinds of LTCC materials mixed with dielectric ceramics in the form of glass + ceramics (multiphase ceramics) [7,8] have been developed, but an approach of glass-ceramics (crystallizable glass) [9,10] were seldom accessed.…”
Section: Introductionmentioning
confidence: 99%